STRES DAN PENYEMBUHAN LUKA PERIODONTAL - Azizah Azizah; Adam Mardiana (Universitas Baiturrahmah, 2021)
Introduction: A periodontal treatment includes surgical and nonsurgical therapy which the successful wound healing after periodontal treatment is influenced by many local and systemic factors. One systemic factor that influences healing is stress. Recent studies have shown that stress plays a role in predicting the severity of pain, periodontal disease, and can even inhibit wound healing. This article aims to review how stress inhibits periodontal wound healing. Review: Stress can occur as a result of stressors or external pressures in the form of household conflicts, financial problems, the death of the closest person referring to emotional and physiological reactions, exceeding one's ability to deal effectively with the situation. The process of healing periodontal tissue is divided into two processes, namely regeneration, and repair. Wound healing in periodontal tissue is the same process that occurs in other parts of the body. Research on the effects of stress on healing periodontal wounds has been carried out. Stress induces glucocorticoid production. Increased cortisol hormone can inhibit the formation of collagen, thinning capillary blood vessels and preventing the formation of new bone. Psychological stress is associated with increased interleukin IL-1β and IL-6 in the gingival crevicular fluid. Other studies have shown that increased stress causes the development of periodontal inflammation due to an increase in IL-1, IL-4, and IL-8 which results in greater periodontal damage. Conclusion: From this literature review it can be concluded that stress inhibits periodontal wound healing.